Enhanced bone marrow stem cell attachment and differentiation on PCL/CNT substrate. Issue 5 (4th May 2019) - Omrani, Maryam Mehdizadeh; Ansari, Mojtaba; Kordestani, Soheila Salahshour; Kiaie, Nasim; Salati, Amir
Abstract: Bone marrow stem cells attracted much attention for cell transplantation therapy of neurodegenerative diseases and injuries of the nervous system. Because of the easy access and the ability of these cells to differentiate into neuronal cells, they can be used to replace damaged neurons in neurodegenerative diseases. With attention to the fact that cell attachment plays a critical role in differentiation process, the aim of this study project is to enhance bone marrow stem cells attachment to PCL scaffold to improve neuronal differentiation. The effect of stiffness of surface on cell attachment has been previously confirmed. In this study, in order to change PCL scaffold stiffness aligned Carbon nanotubes (CNTs) were added to the scaffold and its effect on cell attachment was investigated. CNTs were grown by Plasma Enhanced Chemical Vapor Deposition method on silicon bed. Neuronal morphology assessed by scanning electron microscopy. The stiffness of substrate characterized via atomic force microscopy. Proliferation was assessed by MTT test. The stiffness and protein adsorption were enhanced in PCL/CNTs substrate. Cell proliferation enhanced in these composite substrates.